Pengaruh Persepsi Harga, Lokasi dan Atmosfer Pasar Terhadap Minat Beli Konsumen di Pasar Segiri Kota Samarinda - Riski Riski (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to determine and analyze the influence of price perception, location, and market atmosphere on consumer purchase intention at Segiri Market in Samarinda City, both partially and simultaneously. The background of this research is based on the phenomenon of declining consumer interest in shopping at traditional markets, which has affected traders' income, even though Segiri Market is the main market with a strategic location in the city center. This phenomenon highlights the challenges traditional markets face in maintaining their appeal amid competition from modern markets and shopping malls. Therefore, it is important to explore factors that may influence consumer purchase intention at traditional markets. This research uses a quantitative approach, with data collection techniques through questionnaires distributed to 100 respondents who are visitors of Segiri Market. The collected data were then analyzed using multiple linear regression with the help of SPSS version 27. The results showed that, partially, the location variable had a significant effect on purchase intention, meaning that a strategic location could enhance the market's appeal to consumers. However, price perception and market atmosphere variables did not show a significant effect on purchase intention on their own. Nevertheless, simultaneously, all three variables (price perception, location, and market atmosphere) had a significant impact on consumer purchase intention. These findings have important implications for market managers and local governments to pay more attention to strategic locations and create a comfortable and attractive market atmosphere. This could increase the appeal of traditional markets, attract more visitors, and ultimately help boost traders' income and support the sustainability of traditional markets as part of the local cultural and economic identity.